Experimental investigation of irregular motion impact on 4D PET-based particle therapy monitoring. - Tian, Y.; Stuetzer, K.; Enghardt, W.; Priegnitz, M.; Helmbrecht, S.; Bert, Christoph; Fiedler, F. (Physics in Medicine and Biology, 2016)
Particle therapy positron emission tomography (PT-PET) is an in vivo and non-invasive imaging technique to monitor treatment delivery in particle therapy. The inevitable patient respiratory motion during irradiation causes artefacts and inaccurate activity distribution in PET images. Four-dimensional (4D) maximum likelihood expectation maximisation (4D MLEM) allows for a compensation of these effects, but has up to now been restricted to regular motion for PT-PET investigations. However, intra-fractional motion during treatment might differ from that during acquisition of the 4D-planning CT (e.g. amplitude variation, baseline drift) and therefore might induce inaccurate 4D PET reconstruction results. This study investigates the impact of different irregular analytical one-dimensional (1D) motion patterns on PT-PET imaging by means of experiments with a radioactive source and irradiated moving phantoms. Three sorting methods, namely phase sorting, equal amplitude sorting and event-based amplitude sorting, were applied to manage the PET list-mode data. The influence of these sorting methods on the motion compensating algorithm has been analysed. The event-based amplitude sorting showed a superior performance and it is applicable for irregular motions with ?4 mm amplitude elongation and drift. For motion with 10 mm baseline drift, the normalised root mean square error was as high as 10.5% and a 10 mm range deviation was observed.
EVALuna2:18310